Molecular dynamics study of natural rubber–fullerene composites: connecting microscopic properties to macroscopic behavior. Issue 35 (28th August 2019) - Khuntawee, Wasinee; Sutthibutpong, Thana; Phongphanphanee, Saree; Karttunen, Mikko; Wong-ekkabut, Jirasak
Abstract : Confinement effect of cis -PI at high C60 concentrations. Abstract : Macroscopic and microscopic properties of fullerene (C60 )– cis -polyisoprene ( cis -PI) composites at varying fullerene concentrations were investigated using atomistic molecular dynamics (MD) simulations over microsecond time scales. Results show that the introduction of fullerenes into a polymer matrix increases density, bulk modulus and heat capacity while thermal expansivity decreases. The presence of fullerenes slowed the diffusion of both C60 and cis -PI. Moreover, increasing fullerene concentration results in ordering of the cis -PI chains at the cis -PI–fullerene interfaces and shrinking of bulk PI regions. Free energy calculations of fullerene dimerization suggest that fullerenes disperse at low and aggregate at high fullerene concentrations. Our multi-scaled analysis approach demonstrates the role of 'ordered' regions adjacent to the interface between cis -PI and fullerene in controlling the level of order and mobility of the cis -PI chains. The relationship between the microscopic behavior and the changes in mechanical and thermal properties are discussed. Our study is beneficial for further studies and development of advanced rubber technology for novel, cost-effective, material with very high stiffness and thermal endurance with optimizing conditions of filler contents.